Developing e-Booklet For Online Advertising: A Need Analysis On Enterpreneurship Education - Desy Wahyuningrum Mujiati; Suyitno Muslim; Rina Febriana (research, training and philanthropy institution Natural Aceh, 2021)
Abstract: This research aims to describe the results of the need analysis in developing e-booklet for online marketing in the entrepreneurship subjects. Its need analysis refers to: (1) The great opportunity to become an entrepreneur in the Food & Beverage (F&B) Study Program because of the presence of online sales applications such as Gofood, Grabfood, and the Open PO sales system; (2) The problem of theoretical learning entrepreneurship;(3) The use of the needed media in practicing online marketing. This research uses surveys, observation, in depth interviews, and literature study methods in collecting data. The conducted survey involving 47 alumni of SMK Tata Boga. It showed 96% of them stated that attractive product images can attract consumers; 94% agreed that creating attractive drawings is part of entrepreneurship lessons. The literature study found the book of marketing material is so theoretical. The results on observing the students in class XI and interviewing the entrepreneurship teachers at SMK 1 Tambun Selatan found that: 1) The offline marketing methods are still taught; 2) There is an absence of interactive learning media to make online advertising on product marketing in entrepreneurship subjects. In conclusion, this study emphasizes the needs of interactive learning media in the students’ learning activities. Thus, the findings in this research is beneficial in developing e-booklet as online advertising marketing media in the entrepreneuship education. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan hasil analisis kebutuhan untuk pengembangan media pembelajaran e-booklet pemasaran online di mata pelajaran kewirausahaan. Dalam penelitian ini, analisis kebutuhan mengacu pada: (1) Kesempatan besar menjadi wirausaha pada prodi Tata Boga karena hadirnya teknologi aplikasi penjualan online seperti Gofood, Grab food, dan sistem penjualan Open PO; (2) Masalah pembelajaran kewirausahaan yang bersifat teori; (3) Media yang dibutuhkan dalam praktek pemasaran online. Penelitian ini menggunakan metode survei, observasi, wawancara dan studi literatur dalam mengumpulkan data. Hasil survey yang dilakukan terhadap alumni SMK Tata Boga yaitu 96% menyatakan gambar produk menarik bisa menarik minat konsumen; 94% setuju bahwa membuat gambar yang menarik adalah bagian dari pelajaran kewirausahaan. Hasil studi literatur buku yang digunakan materi pemasaran bersifat teoritik. Hasil pengamatan pada siswa kelas XI Prodi Tata Boga dan wawancara guru kewirausahaan di SMKN 1 Tambun Selatan ditemukan bahwa: 1) Guru masih mengajarkan metode pemasaran Offline; 2) Belum ada media pembelajaran interaktif untuk membuat iklan online pada pemasaran produk di mata pelajaran kewirausahan. Hasil penelitian ini menyimpulkan bahwa siswa memerlukan media pembelajaran interaktif dalam kegiatan pembelajaran. Dengan demikian, penelitian ini digunakan dalam mengembangkan media e-booklet pemasaran iklan online pada mata pelajaran kewirausaaahan.